Who was the author of the first Baltic book? Hypothesis - Lemeškin, Ilja (Baltistica, 2019)
The article is dedicated to an early printed book from 1545, i.e. the anonymous German-Old Prussian catechism, which is considered to be the first printed Baltic book. The analysis of the introduction of the book allows to come up with a hypothesis that the book was compiled by David Reiman, matriculated at the Königsberg Academy in 1544 as Dauid Reiman, Prutenus.